1989
DOI: 10.1007/bf02374386
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and time-response assessments ofHeterorhabditis heliothidis andSteinernema feltiae [Nem.: Rhabitida] againstAedes aegypti larvae

Abstract: Steinernema feltiae (= Neoaplectana carpocapsae) andHeterorhabditis heliothidis were tested against 3 "d instar Aedes aegypti larvae in the laboratory. Different dosages of the nematodes and varying durations of exposure were assessed. H.heliothidis was more effective than S.feltiae. Larval mortality showed a positive linear correlation with both nematode dosage and the duration of exposure. The number of nematodes of both species that gained access to the haemocoele of larvae was always low, but increased wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
5
0
2
Order By: Relevance
“…The feeding is indiscriminate because larvae eat consume different species of EPN as well as dead and live EPNs. Our studies also showed that larval mortality was dose dependent with greater and more rapid mortality caused by higher EPN concentrations as indicated in previous experiments (Molta and Hominick, 1989;Poinar and Kaul, 1982;Cagnolo and Almirón, 2017;Chaudhary et al, 2017;Aiswarya et al, 2018). These findings are in line with those reported for other insects or insect life stages commonly found in terrestrial habitats (Georgis et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…The feeding is indiscriminate because larvae eat consume different species of EPN as well as dead and live EPNs. Our studies also showed that larval mortality was dose dependent with greater and more rapid mortality caused by higher EPN concentrations as indicated in previous experiments (Molta and Hominick, 1989;Poinar and Kaul, 1982;Cagnolo and Almirón, 2017;Chaudhary et al, 2017;Aiswarya et al, 2018). These findings are in line with those reported for other insects or insect life stages commonly found in terrestrial habitats (Georgis et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Welch (1961) and Welch and Bronskill (1962) were the first to demonstrate that EPNs infect the larvae of the mosquito, Aedes aegypti, in the laboratory and field. Studies by Welch (1961), Poinar and Leutenegger (1971), Finney and Harding (1981), Poinar and Kaul (1982) and Molta and Hominick (1989) generally showed that EPNs infected and killed mosquito larvae, but a number of factors such as damage to the IJs during ingestion, immune responses, and spatial separation of the host and EPNs affected their efficacy. More recently, Cagnolo and Almiron (2010) reported that 75% of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…The lower susceptibility of earlier instar larvae may be due to their small mouthparts or feeding behavior that excludes large particles (Bedding et al, 1983). The IJs are difficult to penetrate directly through the cuticle or pores in the 1 st and 2 nd instar larvae with very small body sizes (Molta and Hominick, 1989;Ulvedal et al, 2017). For some detail, large-sized hosts could more readily ingest IJs without damaging them, while smallsized early instar larvae rarely ingest IJs, more often crushing them with their mandibular teeth because of their smaller oral aperture.…”
Section: Developmental Stage and Physiology Of The Insect Host As Key...mentioning
confidence: 99%